2020
DOI: 10.24908/pceea.vi0.14157
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Development of Critical Reflection Skills in First-Year Engineering Informed Through Student Perspectives

Abstract: Reimagined curriculum models offer new possibilities for embedding durable competencies into the curriculum, including critical reflection, which promotes the development of self-directed learning skills. However, students often perceive these skills as unimportant with pre-existing biases focusing on technical content as the core of engineering.  The primary goal of this work was to identify key considerations when integrating critical reflection into engineering curricula, specifically in the context of firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The understanding of the importance of reflexivity in engineering education is growing. As described by DaMaran, Pearlston, and Mattucci [20],…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the importance of reflexivity in engineering education is growing. As described by DaMaran, Pearlston, and Mattucci [20],…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified that there may be progressive 'stages' in development of one's reflective practice [5]. Despite these findings not being validated, students will begin the course at different levels of reflective competencies.…”
Section: Next Stepsmentioning
confidence: 93%
“…Previous research has identified considerations for implementing critical reflection into the first-year engineering curricula in ways that students will meaningfully engage [5]. Student focus groups were performed with two student populations: experienced reflectors (campus wide), and first-year engineers.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation